Konsep Bukaan dan Orientasi Bangunan sebagai Bentuk Penerapan Arsitektur Bioklimatik pada Desain Sportorium di Pesantren Mangkoso Barru - Muasyarah, Hasanatul; Marwati, Marwati; Herniwati, Andi (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2024)
Abstract_ The increasingly severe global climate change, triggered by human activities such as fossil fuel combustion, deforestation, and industrial activities, has created an urgency to design buildings that are more efficient and environmentally friendly. Global warming, caused by the increase in greenhouse gas concentrations in the atmosphere, necessitates the application of new approaches in building design, which not only focus on reducing energy consumption but also on overall environmental sustainability. This research aims to identify the application of bioclimatic architecture principles in building design, focusing on orientation, openings, and material selection that support energy efficiency. The methods used in this research include descriptive analysis of passive solar design that utilizes natural energy from the surrounding environment, the selection of sustainable materials, and the implementation of green systems such as green roofs and rainwater harvesting systems to reduce the building's carbon footprint. The research results indicate that the application of bioclimatic architecture principles, such as optimal building orientation towards the sun and efficient use of openings, can reduce dependence on artificial energy, enhance occupant comfort, and minimize negative environmental impacts. These findings support climate change mitigation efforts by creating buildings that are more energy-efficient, sustainable, and environmentally friendly.